Theravada traditions: Buddhist ritual cultures in contemporary Southeast Asia and Sri Lanka - Holt, John Clifford (University of Hawaiʻi Press, 2017)
Phra Bang : venerating the Buddha image in Lao religious culture -- Asala Perahara : powers of the Buddha relic in Sri Lanka -- Upasampada and pabbajja : ordination in Thai Buddhist contexts -- Kathina : making merit in modern Myanmar (Burma) -- Pchum Ben : caring for the dead ritually in Cambodia